Teatro e educação em tempos sombrios: o caráter político-pedagógico do grupo teatro União e Olho Vivo - Gabriel, André Luís (2013)
The relationship between education and theater is fruitful. This paper addresses this issue in the historical perspective to check the political teaching of the Group Teatro União e Olho Vivo, a group that makes choice of popular and amateur theater and among many journeys in his more than four decades of existence was an integral part among those who resisted and acted so engaged during the so-called "years of lead" of civil-military dictatorship in Brazil in the 1960s and 1970s. Are numerous and diverse orders the questions about the current context of education, educational policy, teaching methodologies, on the curriculum components, finally, about their dilemmas and challenges. This work borrows the voice of important historical subjects, notably the lawyer Idibal Pivetta and playwright Cesar Vieira, acting under another range of situations, which in addition to embrace the context quoted, still has the bias of censorship, political persecution and ideological components as also present in the everyday life of teachers, students, artists, etc. the period taken as a historical period. Through interviews and testimony and under the benchmark historical cultural specificities of education (policies, legislation and educational aspects of teaching methodologies) and the arts, especially the theater that is an integral part of our corporate research and some of its possibilities and particularities (collective creation, political and educational, folk, amateur theater) make up the backbone of this work.